Design and Trial of Chemistry Pocketbook Contained Science Generic Skills - Susanti, Susi; Ritonga, Pangoloan Soleman (Tarbiyah : Jurnal Ilmiah Kependidikan, 2021)
This research aimed at developing a pocket book containing science generiC skills on Reaction Rate lesson and knowing validity level, practicality level, and student response to the developed pocket book.  It was Research and Development (R&D) with Borg and Gall model.  The subjects of this research were 10 the twelfth-grade students of Natural Science 3 at Islamic Senior High School of Darul Hikmah Pekanbaru. The object was the pocket book containing science generik skills on Reaction Rate lesson. Validity test questionnaire, practicality test questionnaire, student response test questionnaire, interview, and documentation were the techniques of collecting the data. Analyzing the data was done by using qualitative and quantitative descriptive analysis techniques.  The research findings showed that the validity level of the chemistry pocket book was 76.3% (valid), the practicality level was 81.2% (very practical), and the percentage of student response to the pocket book was 84.2% (very good).  It could be concluded that the chemistry pocket book containing science generik skills on Reaction Rate lesson could be tested wider.